2008
DOI: 10.1136/bjsm.2007.044826
|View full text |Cite
|
Sign up to set email alerts
|

Vo2requirement at different displayed power outputs on five cycle ergometer models: a preliminary study

Abstract: Inaccuracies between -10% and 18% in displayed PO of various cycle ergometers question their interchangeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The oxygen cost for a given workload display has been shown to vary by j10% and 18% on popular ergometers (16). The SRM Power Meter has an average factory error of 2.3% T 4.9%, which can be reduced to j0.8% T 1.7% by performing a dynamic calibration as described by Gardner et al (15).…”
Section: Discussionmentioning
confidence: 98%
“…The oxygen cost for a given workload display has been shown to vary by j10% and 18% on popular ergometers (16). The SRM Power Meter has an average factory error of 2.3% T 4.9%, which can be reduced to j0.8% T 1.7% by performing a dynamic calibration as described by Gardner et al (15).…”
Section: Discussionmentioning
confidence: 98%
“…However, it should be noted that an ergometer presenting validity determined by direct dynamic calibration may not present concurrent validity in relation to a gold standard ergometer because of errors [29] between the same gas analysis systems. However, 5 brands of cycle ergometers were evaluated [7] by comparing the VO 2 requirements at diff erent displayed power. Large diff erences (5 -10 mL • kg − 1 • min − 1 ) at the same displayed power indicate inaccuracy of displayed power output.…”
Section: Discussion ▼mentioning
confidence: 99%
“…Using corrected power values from the standard dynamometer revealed that for the same VO 2 the power output was underestimated by 15 W for the Monark. The researchers [7] did not consider the error of gas analysis systems. Thus, the results of this study derived from the diff erent statistical analyses permit to infer that the gas analysis system was reliable for the 2 ergometers.…”
Section: Discussion ▼mentioning
confidence: 99%
“…While readily available, bicycle ergometers should be treated with care. There is variation between bicycle ergometers [65] and the validity of bicycle ergometers during incremental power tests can be lower than expected compared to steady-state exercise tests [66]. The determination of power output could be inaccurate [7], as was demonstrated in some "turbo trainers" [67].…”
Section: Measurements On a Wcementioning
confidence: 99%